Perubahan Fungsi Rumah Gadang di Nagari Tuo Pariangan Kabupaten Tanah Datar - Azhariyatul Huda; Rina Susanti (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
This research aims to understand the changes in the function of the traditional Minangkabau house (rumah gadang) in Nagari Tuo Pariangan, Tanah Datar Regency. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation, as well as qualitative data analysis using the Miles Huberman model. The main research subjects are five individuals selected using purposive sampling, supplemented by two additional subjects, namely the village head and the head of Nagari Tuo Pariangan's tourism awareness group (pokdarwis). The findings indicate that clan members initially used the rumah gadang as a residence, a place for deliberation and consensus, a gathering place for relatives, a venue for traditional ceremonies, a symbol, and also served an educational function. However, the designation of Nagari Tuo Pariangan as a tourist village has shifted the use of rumah gadang to homestays or lodgings. As a result, rumah gadang now primarily houses clan representatives, serves as a venue for large-scale deliberations, and no longer functions as a gathering place for relatives. Instead, it now serves as a business hub, generating economic value for the clan members. The transformation of rumah gadang into homestays is primarily due to the fact that many clan members have relocated to seek their fortune elsewhere, and others have chosen to construct their own homes outside of the rumah gadang. External factors contributing to the change include the awards received by Nagari Tuo Pariangan as the most beautiful village and the developing tourist village award, as well as encouragement from the local tourism awareness group (pokdarwis) in Nagari Tuo Pariangan.